Smartphone use behavior in students - Sinurat, Samfriati; Novitarum, Lilis; Tamba, Vebita C (International Journal on ObGyn and Health Sciences, 2023)
Almost every individual teenager nowadays has a smartphone. The use of this smartphone can have a positive and negative impact on their behavior which will affect their development and learning success. Smartphone use behavior has positive benefits if teenagers can use it well to facilitate communication and access information, including in learning media so that they are more creative. But do not refuse the use of smartphones often play smartphones from learning and interacting with the surrounding environment. Continuous use of smartphones will have a negative impact on adolescent behavior such as reduced social characteristics in students, reduced student interaction patterns, consumptive nature that causes students to commit crimes to addiction to the internet, games, and also pornographic content. The purpose of this study was to determine the behavior of using smartphones in junior high school students. This type of research is descriptive. Sampling in this study used a total sampling technique, where the number of samples was 80 people. The instrument used in this study was a questionnaire (smartphone usage behavior). The results of the research on the behavior of using smartphones in students who were categorized as adequate were 68 people (85.0%), and 12 people were categorized as good (15%). It is expected that respondents can use smartphones for positive things such as studying and finding information related to learning.